Overcoming Bottlenecks of Enzymatic Biofuel Cell Cathodes: Crude Fungal Culture Supernatant Can Help to Extend Lifetime and Reduce Cost. Issue 7 (25th June 2013) - Sané, Sabine; Jolivalt, Claude; Mittler, Gerhard; Nielsen, Peter J.; Rubenwolf, Stefanie; Zengerle, Roland; Kerzenmacher, Sven
Abstract Enzymatic biofuel cells (BFCs) show great potential for the direct conversion of biochemically stored energy from renewable biomass resources into electricity. However, enzyme purification is time‐consuming and expensive. Furthermore, the long‐term use of enzymatic BFCs is hindered by enzyme degradation, which limits their lifetime to only a few weeks. We show, for the first time, that crude culture supernatant from enzyme‐secreting microorganisms (Trametes versicolor) can be used without further treatment to supply the enzyme laccase to the cathode of a mediatorless BFC. Polarization curves show that there is no significant difference in the cathode performance when using crude supernatant that contains laccase compared to purified laccase in culture medium or buffer solution. Furthermore, we demonstrate that the oxygen reduction activity of this enzymatic cathode can be sustained over a period of at least 120 days by periodic resupply of crude culture supernatant. This is more than five times longer than control cathodes without the resupply of culture supernatant. During the operation period of 120 days, no progressive loss of potential is observed, which suggests that significantly longer lifetimes than shown in this work may be possible. Our results demonstrate the possibility to establish simple, cost efficient, and mediatorless enzymatic BFC cathodes that do not require expensive enzyme purification procedures. Furthermore, they show the feasibility of an enzymatic BFC with an extended lifetime, in which self‐replicating microorganisms provide the electrode with catalytically active enzymes in a continuous or periodic manner.